Исследование структуры рабочей поверхности абразивных композиционных материалов путем разработки метода расчета количества активных компонентов - Сафонова, М.Н.; Шиц, Е.Ю.; Сыромятникова, А.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
А сalculation-experimental methods for evaluation of active abrasive grain number with statistically uniform distribution in composition material was developed. The method was used to study the change of active grains concentration of natural and synthetical diamond grinding powders with various dispersions in PTFE-based composite under friction and wear.